ACR appropriateness Criteria® pediatric Hodgkin lymphoma. Issue 7 (24th February 2014) - Terezakis, Stephanie A.; Metzger, Monika L.; Hodgson, David C.; Schwartz, Cindy L.; Advani, Ranjana; Flowers, Christopher R.; Hoppe, Bradford S.; Ng, Andrea; Roberts, Kenneth B.; Shapiro, Ronald; Wilder, Richard B.; Yunes, Michael J.; et al.
<x xml:space="preserve">Abstract</x> Pediatric Hodgkin lymphoma is a highly curable malignancy and potential long‐term effects of therapy need to be considered in optimizing clinical care. An expert panel was convened to reach consensus on the most appropriate approach to evaluation and treatment of pediatric Hodgkin lymphoma. The American College of Radiology Appropriateness Criteria are evidence‐based guidelines for specific clinical conditions that are reviewed every 2 years by a multidisciplinary expert panel. The guideline development and review include an extensive analysis of current medical literature from peer reviewed journals and the application of a well‐established consensus methodology (modified Delphi) to rate the appropriateness of imaging and treatment procedures by the panel. In those instances where evidence is lacking or not definitive, expert opinion may be used to recommend imaging or treatment. Four clinical variants were developed to assess common clinical scenarios and render recommendations for evaluation and treatment approaches to pediatric Hodgkin lymphoma. We provide a summary of the literature as well as numerical ratings with commentary. By combining available data in published literature and expert medical opinion, we present a consensus to the approach for management of pediatric Hodgkin lymphoma. Pediatr Blood Cancer 2014;61:1305–1312. © 2014 American College of Radiology.